Direct Genotypic Characterization of Toxoplasma gondii Strains Associated with Congenital Toxoplasmosis in Tunisia (North Africa) - Boughattas, Sonia (The American Society of Tropical Medicine and Hygiene, 2010)
Here, we determined the Toxoplasma gondii genotype in amniotic fluid, placenta, and cerebrospinal fluid samples from 14 congenital toxoplasmosis cases in Tunisia, North Africa. Direct genotypic characterization of T. gondii strains was performed by polymerase chain reaction (PCR) amplification of six genetic markers (3′SAG2, 5′ SAG2, SAG3, BTUB, GRA6, and APICO) and thereafter, was analyzed by restriction fragment-length polymorphism (RFLP). Samples were sequenced to resolve strain type whenever there were unclear enzyme digestion results. Multilocus analysis revealed that only one specimen harbored the type I allele in all studied loci, whereas the 13 others gave mixed genotype results with different alleles at different markers. Seven specimens produced RFLP profile of the recombinant strains I/III, and three produced a profile of I/II recombinant strains. The last three specimens produced complex digestion patterns. In these cases, sequence analysis revealed double peaks at known polymorphic sites, indicating the presence of multiple alleles.